Türkiye’de din adamının sosyal statüsü - Adıyaman, Kadir (My University, 2003)
Araştırmamız üç bölümden oluşmaktadır. Birinci ve ikinci bölümlerde din. Dinin fonksiyonları, din adamı, din adamının eğitimi, sosyal statüsü, normlar, statü, rol, pozisyon, yetki, sorumluluk ve prestij konuları dokümantasyon metoduyla elde edilen bilgiler ışığında değerlendirilmiştir. Üçüncü bölümde, Türkiye'de din adamının sosyal statüsü, din görevlileri ve halkın görüşlerine müracaat etmek suretiyle uygulamalı bir araştırma yapılmıştır. Bu bölümde anket (survey) metodu kullanılmıştır. Türkiye'de din adamının sosyal statüsü tespit edilmeye çalışılmıştır. Çıkan sonuca göre din adamı en başta görülme isteğinin yanında, normal memur statüsünde görülmektedir. Bunun sebepleri olarak da, din adamının eğitiminin yetersiz olduğu, gelişen ve değişen dünyadaki gelişmeleri takip edemediği, ekonomik problemleri olduğu, toplumla iletişim konusunda problemler yaşadığı ortaya çıkmıştır. Din adamının toplumda arzu edilen bir statüyü yakalayabilmesi için mutlaka İlahiyat Fakültesi mezunu olması, ihtisas yapmasının özendirilmesi, hizmet içi eğitim kurslarına katılması, ekonomik olarak rahatlatılması gerekmektedir. Yapılması gerekenler yapıldığında, toplumun ihtiyaçlarına daha güzel cevap vereceği ve statüsünün de olması gereken yere yükseleceği düşünülmektedir. Our investigation consists of three sections. In the first and second section, the subjects of the functions of religion, religious officer, the education of the religious officer, his social status, norms, status, role, position, authority and responsibility and prestige have been evaluated in the lights of the information gathered by the method of documentation. In the third part, an applied research has been made about the social status of the religious officer in Turkey, resorting to the ideas of the religious officers and the ordinary people. In that section the survey method was used. By doing that, we tried to learn the social status of the religious officer in Turkey. According to the result of this survey, we see that there are some people who want to see the religious officer at the top level as well as there are some people who want to see them as ordinary civil servants . As the reasons lying behind the latter wish, we come accross the facts that the education of the religious officer is not adequate, unfortunately the religious officer cannot keep up with the developments in the changing and developing world, he has economic problems, he has communication problems in the soceity. In order to attain the desired status in the society for the religious officer, it is required that he gets graduate from university, he is encouraged to specialize in a particular subject, attends some courses and gets some relief in respect of economy. When all these are done, I think that the religious officer will meet the needs of the society and ascend to the longed position and reputation.
Keywords: Din; Din Adamları_Türkiye; İslam Dini; Tasavvuf ve tarikatlar